2007
DOI: 10.1080/13603110600790340
|View full text |Cite
|
Sign up to set email alerts
|

The grassroots community in the vanguard of inclusion: the post‐genocide Rwandan prospects

Abstract: More than a decade has passed since Rwanda was plunged into the most atrocious genocide of our time. Hundreds of thousands of lives were lost and many more were left in desperate conditions. The economic and social reconstruction of the country has since dominated the national agenda for recovery. It is within this reform agenda that this paper looks at the situation of the post-genocide young people with disabilities and the possible pathways for their inclusion. It points out that it is not all gloomy news. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…To fight ingrained cultural stereotypes within the context of Afghanistan, the CBR program has been advocating for the rights to access services for persons disabled at birth, particularly in remote areas as a way to promote their overall wellbeing. The stigma of disability has been shown to limit access to healthcare [7,75] and access to school [76,77], reducing opportunities to make friends and build a family life [78], resulting in mental distress [79].…”
Section: Discussionmentioning
confidence: 99%
“…To fight ingrained cultural stereotypes within the context of Afghanistan, the CBR program has been advocating for the rights to access services for persons disabled at birth, particularly in remote areas as a way to promote their overall wellbeing. The stigma of disability has been shown to limit access to healthcare [7,75] and access to school [76,77], reducing opportunities to make friends and build a family life [78], resulting in mental distress [79].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there is paucity of literature linking stigma to such common mental disorders (Alonso, et al 2008;Baxter, et al 2013). Studies have shown that stigma -the combination of stereotypes, negative attitudes and discrimination or social exclusion-towards disability constitutes a barrier to service use (Maulik and Darmstadt 2007), access to school (Cooney, et al 2006;Karangwa, et al 2007), participation in employment (Mitra and Sambamoorthi 2008) and jeopardizes the possibility for persons with disabilities to make friends and achieve family life (Green 2003). Stigma is jeopardizing a general principle stated in article 3 of the 2006 United Nations Convention for the Rights of Persons with Disabilities (UNCRPD), which stipulates that persons with disabilities have a right to "full and effective participation and inclusion in society" (United Nations 2006).…”
Section: Effect Of Stigma Associated With Disabilitymentioning
confidence: 99%
“…Since 2000, the Rwandan government has formulated policies to enhance the rights of people with disabilities, trained teachers and community leaders on effective, age-appropriate, culturally responsive pedagogies and streamlined collaboration among grassroots NGOs and international bodies, all with the aim of improving the educational experiences of pupils with disabilities. Research suggests that inclusion in its fullest sense is important for Rwanda's advancement, from a political and human rights perspective (Karangwa, Miles, and Lewis 2010;Karangwa, Ghesquiere, and Devlieger 2007). In light of this, private-sector institutions and non-governmental organisations have increased their support for inclusive education.…”
Section: Mapping the Margins In Different Fields: Exploring Gender Inmentioning
confidence: 99%